Benefits and Spillover Effects of Infrastructure: A Spatial Econometric Approach - Kijin Kim; Junkyu Lee; Manuel Leonard Albis; Ricardo III B. Ang (East Asian Economic Review (EAER), 2021)
This paper estimates the effects of transport (road and rail) & energy and ICT infrastructure (telephone, mobile, and broadband) on GDP growths in neighboring countries as well as own countries. We confirm positive direct contributions of infrastructure, access to Internet, and human capital on economic growth. The spatial panel regression models indicate that there exist positive externalities of the broadband infrastructure and human capital, and these results are robust regardless of the choice of spatial weight matrices. Our findings on spillover effects of infrastructure suggest the key role of neighboring countries' infrastructure on own country's economic growth.
Keywords: C21; D24; D62; 330; Infrastructure; Spillover Effects; Economic Growth; Production Function; Spatial Econometrics